2011
DOI: 10.1111/j.1526-100x.2011.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspen and Willow Restoration Using Beaver on the Northern Yellowstone Winter Range

Abstract: Aspen (Populus tremuloides) on the northern Yellowstone winter range has declined over the last half-century. Beaver (Castor canadensis) were reintroduced in Eagle Creek in 1991 in an attempt to reverse this trend. In 2005, we assessed the efficacy of this project by quantifying the long-term effects of beaver on aspen stands and the riparian area in this drainage. Between 1990 and 2005, the canopy cover of mature aspen decreased more than 62%, whereas immature aspen cover more than tripled, resulting in a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…These photos were obtained from the U.S. Department of Agriculture and had a 1‐m resolution and 5‐m accuracy. The 29‐ha 2 digital polygon used in McColley et al's () study was used to delineate the riparian corridor of Eagle Creek in the photos. Three hundred random points per photo were generated within the polygon and visually classified into a cover type category according to the dominant cover type at each point.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These photos were obtained from the U.S. Department of Agriculture and had a 1‐m resolution and 5‐m accuracy. The 29‐ha 2 digital polygon used in McColley et al's () study was used to delineate the riparian corridor of Eagle Creek in the photos. Three hundred random points per photo were generated within the polygon and visually classified into a cover type category according to the dominant cover type at each point.…”
Section: Methodsmentioning
confidence: 99%
“…McColley et al () found that beaver activity in Eagle Creek decreased the mature aspen canopy cover by 62% from 1990 to 2005, while immature aspen cover more than tripled during this same time period. Willow ( Salix spp.)…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations